IMPLEMENTATION OF THE FIRE EMERGENCY RESPONSE SYSTEM AT DR. TADJUDDIN CHALID MAKASSAR - Sulaiman , Ahmad; Rizkya, Elvira Wanda; Mubarak, Muhammad Hosni (Yayasan Nuraini Ibrahim Mandiri, 2024)
The growth and arrangement of existing buildings is often not balanced with the readiness of building infrastructure or gives the impression of forced development so that the resulting physical buildings pay little attention to fire hazards. Fire prevention is a building system that aims to save lives and property from the dangers of fire. Preparedness and handling before a fire occurs is a very important factor in preventing fires. The aim of this research is to see whether the implementation of the emergency response system at RSUP Dr. Tadjuddin Chalid Makassar is in accordance with standards. This research method uses qualitative research with a descriptive approach through in-depth interviews. The informants for this research are the person in charge of K3RS, Head of Sanitation Installation, members of the hospital emergency response team , hospital fire brigade team, hospital management team and Head of Facilities and Infrastructure Maintenance. The research results showed that RSUP Dr. Tadjuddin Chalid Makassar has implemented a fire emergency response system that is in accordance with standards, but it is not yet optimal, such as evaluation of training and education that has not been implemented, in the active fire system there are still APARs that have expired and several hydrants that are not attached with instructions for use, then in the system passive fires, there are still gathering places that are still used as parking lots and there are no emergency stairs specifically for patients who use wheelchairs. Keywords : System, Response, Emergency, Fire, Hospital